2020
DOI: 10.12659/msm.920325
|View full text |Cite
|
Sign up to set email alerts
|

Asiaticoside Alleviates Cerebral Ischemia-Reperfusion Injury via NOD2/Mitogen-Activated Protein Kinase (MAPK)/Nuclear Factor kappa B (NF-κB) Signaling Pathway

Abstract: Background: Cerebral ischemia-reperfusion injury (CIRI) remains a serious health problem. Centella asiatica formulations are used to treat central nervous system disorders. In the present study, asiaticoside, an extract of the plant Centella asiatica, was investigated in CIRI in vivo and vitro. Material/Methods: We made a CIRI model in vivo in SD rats treated by middle cerebral artery occlusion, and a cell model of ischemiareperfusion injury was made in PC12 cells treated by deprivation of oxygen and glucose/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…A key pathway of inflammation in central nervous system injury is the NF-κB pathway, which regulates the expression of pro-inflammatory and pro-apoptosis genes in its active form ( Howell and Bidwell, 2020 ). Neuroprotective effect may be achieved by regulating MAPK and NF-κB signaling pathways and thus regulating inflammatory responses ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A key pathway of inflammation in central nervous system injury is the NF-κB pathway, which regulates the expression of pro-inflammatory and pro-apoptosis genes in its active form ( Howell and Bidwell, 2020 ). Neuroprotective effect may be achieved by regulating MAPK and NF-κB signaling pathways and thus regulating inflammatory responses ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the degradation pathways of the monoamine neurotransmitter precursors have been reported to be activated by inflammatory factors, which may lead to an increase in the levels of these neurotransmitters ( 10 ). A previous study also showed that asiaticoside exhibited a strong anti-inflammatory effect in animal models of cognitive deficits, spinal cord injury and cerebral ischemia-reperfusion injury ( 27 , 33 , 34 ). In the present study, it was demonstrated that CMS increased hippocampal IL-1β, IL-6 and TNF-α levels, which were alleviated by asiaticoside administration, thus indicating that the antidepressant effect of asiaticoside may be due to its anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, it was demonstrated that asiaticoside inhibited the activation of pNF-κBp65, NLRP3 and caspase-1, leading to a reduction in the levels of inflammatory cytokines and subsequent inflammatory response. It has also been reported that asiaticoside may attenuate inflammation by downregulating pNF-κBp65 and the levels of inflammatory cytokines, such as IL-1β, IL-6 and TNF-α, in a rat model of β-amyloid-induced Alzheimers disease ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention and treatment of CIRI have gained increased attention in the field of global IR research ( 24 , 25 ). Blocking neuronal apoptosis is the most important step in alleviating CIRI ( 26 ).…”
Section: Discussionmentioning
confidence: 99%